Modelling Organizational Support to Shape Knowledge Sharing Behavior - Budiyono, Haris; Ekowati, Ekowati (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study examines the determinants of knowledge-sharing behavior among faculty, focusing on the role of organizational support. It contributes to knowledge management literature by clarifying how organizational support translates into knowledge-sharing through individual initiative and technological capability in academic settings. Using a quantitative explanatory design, data from 150 faculty members were analyzed with Structural Equation Modeling. The findings show that organizational support significantly enhances individual initiative, technological capability, and knowledge-sharing behavior, while individual initiative partially mediates this relationship. Technological capability also directly strengthens knowledge-sharing practices. These results position organizational support as a foundational driver that operates through both human and technological mechanisms. The study implies that higher education institutions should strengthen support systems, invest in technological infrastructure, and foster proactive individual initiatives to sustain effective knowledge-sharing cultures.